Squamous Cell Lung Cancer with Cutaneous Metastases: A Case Report - Haryati, Haryati; Tanjung, Efrilia (Indonesian Journal of Cancer, 2025)
Introduction: The prevalence of lung cancer accompanied by skin metastases ranges from 1% to 12%, with the highest occurrence observed in males with adenocarcinoma and large cell types are more frequent, whereas squamous cell carcinoma (SCC) exhibits a lower propensity for this behavior. Skin metastases are frequently indicative of a negative prognostic determinant. It may serve as the initial sign in highly unusual conditions.Case Presentation: A 60-year-old male who has smoked his entire life is experiencing a persistent dry cough and a solitary nodule located in the right mental area. The skin lesion had persisted for 1 month, exhibiting an enlarged size and a heightened ulceration. The chest CT imaging revealed the presence of a semisolid mass in the left lower lobe, measuring 11x7x15 cm, accompanied by lymphadenopathy in the left parahilar and subcarinal regions. Squamous cell cancer (SCC) has been identified from lung and skin biopsy. P40 was detected in the immunohistochemistry analysis. A regimen of systemic chemotherapy using carboplatin and docetaxel was initiated. He exhibited an unfavorable response to chemotherapy following two courses of treatment and died of the disease 5 months after the manifestation of symptoms.Conclusion: The occurrence of lung cancer with skin metastases, particularly SCC, is infrequent. Metastases should be taken into consideration as a potential diagnosis in patients presenting with skin lesions and a smoking history. The skin symptoms observed upon initial diagnosis indicate a poor prognosis, with a median survival period of 3 to 5 months. Early examination holds significant importance